Evaluation of Nuchal Translucency Measurement in First Trimester Pregnancy - Barati, Mojgan (Royan Institute, 2011)
BACKGROUND: A significant number of pregnancies, particularly in women with previous histories of infertility, are associated with fetal abnormalities. Methods such as the nuchal translucency (NT) measurement enable us to identify more pregnancies with chromosomal abnormalities. MATERIALS AND METHODS: This analytic cross-sectional study was performed in 446 pregnant women at 11-14 weeks gestation, from 2009 to 2010 in the Fetal Medicine Unit of Imam Khomeini Hospital, Ahvaz Jundishapur University of Medical Sciences. All NT measurements were performed by a certified sonographer using the Fetal Medicine Foundation (FMF) recommended protocol. FMF first trimester software was used for primary and secondary (adjusted) risk calculation. RESULTS: The average maternal age was 28.5 years and 15% of mothers were ≥35 years of age. The average crown rump length (CRL), gestational age and NT thickness were 61.7, 12.4 weeks and 1.75 mm, respectively. There were 20 cases with increased adjusted risk (4.04%) and 4 cases of documented abnormal karyotype. CONCLUSION: In our study increased adjusted risk was 4.04%.Documented abnormal karyotype were 0.9% and 28% of total and high-risk groups who accepted amniocentesis, respectively. In this study, 50% of women with high-risk results and about half of those with abnormal karyotypes were seen in women under age 35. Knowing these risks is of utmost importance in pregnancy, particularly in patients with infertility histories.